The Solutions of Non-linear Wave Equations by Variational Iteration Method (College of Basic Education Research Journal, 2026)
Abstract: This paper utilizes the Variational Iteration Method to address non-linear wave equations. This study provides approximate analytical solutions for both homogeneous and non-homogeneous non-linear wave problems. Moreover, the study provided specific analytical solution formulas for specific cases, which allowed for the determination of the analytical solution without the need for successive iterative operations. Furthermore, this study provided a range of various solved examples and compared the approximate solution with the analytical solution.
Keywords: Approximate analytical solution; nonlinear wave equations; Variational Iteration method